2007
DOI: 10.1603/0022-2585(2007)44[175:iritbb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Resistance in the Bed Bug: A Factor in the Pest’s Sudden Resurgence?

Abstract: Infestations of the bed bug, Cimex lectularius L. (Heteroptera: Cimicidae), are increasing around the world at an alarming rate and have become a major public health concern. The evolution of insecticide resistance could be a primary factor in explaining this resurgence. Extremely high levels of resistance to two pyrethroid insecticides, deltamethrin and lambda-cyhalothrin, relative to a susceptible colony, were detected in populations collected from human dwellings in Kentucky and Ohio. Offspring of a cross b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
134
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(136 citation statements)
references
References 12 publications
2
134
0
Order By: Relevance
“…2 Their cryptic nature and increasing resistance to a large variety of insecticides makes them difficult to detect and even more difficult to eliminate. 6 In addition, the high cost and limited effectiveness of treatment methods may restrict community efforts to exterminate them, 7 and may create an economic burden on affected communities and local governments. 8 Current evidence suggests numerous pathways for bed bug dispersal.…”
Section: Introductionmentioning
confidence: 99%
“…2 Their cryptic nature and increasing resistance to a large variety of insecticides makes them difficult to detect and even more difficult to eliminate. 6 In addition, the high cost and limited effectiveness of treatment methods may restrict community efforts to exterminate them, 7 and may create an economic burden on affected communities and local governments. 8 Current evidence suggests numerous pathways for bed bug dispersal.…”
Section: Introductionmentioning
confidence: 99%
“…Bed bugs become very active in the summer season, especially in August and September when the infestation reaches its peak. In the winter, January and February, the lowest infestation rate of bed bugs is recorded in the year [13]. See Figure 4 for more details.…”
Section: Time Variation (Time)mentioning
confidence: 99%
“…According to the latest available data, the infestation peaked in 2010 (Figure 2). Although, Romero et al (2007) mentioned that bed bug infestation has not reach its peak yet. It will record new peaks in the coming few years, and the escalation of this infestation seems to be inevitable [12].…”
Section: Time Variation (Time)mentioning
confidence: 99%
“…Bed bugs indiscriminately infest buildings regardless of low-or high-income homes (98%), luxury hotels or motels (75%), College dorms (47%) or nursing homes (46%) [1]. The bed bug resurgence was attributed to an increase in international travel and trade, and use of less toxic insecticides [2][3][4]. The U.S. Department of Commerce reported that there were 51 million international tourists in 2000, a 15% increase over a period of 1995-2000 [4].…”
Section: Introductionmentioning
confidence: 99%